Prior inpatient admission increases the risk of post‐operative infection in hepatobiliary and pancreatic surgery. Issue 12 (3rd September 2015) - Dong, Zachary M.; Chidi, Alexis P.; Goswami, Julie; Han, Katrina; Simmons, Richard L.; Rosengart, Matthew R.; Tsung, Allan
Abstract: Background: Hepatobiliary and pancreatic (HPB) operations have a high incidence of post‐operative nosocomial infections. The aim of the present study was to determine whether hospitalization up to 1 year before HPB surgery is associated with an increased risk of post‐operative infection, surgical‐site infection (SSI) and infection resistant to surgical chemoprophylaxis. Methods: A retrospective cohort study of patients undergoing HPB surgeries between January 2008 and June 2013 was conducted. A multivariable logistic regression model was used for controlling for potential confounders to determine the association between pre‐operative admission and post‐operative infection. Results: Of the 1384 patients who met eligibility criteria, 127 (9.18%) experienced a post‐operative infection. Pre‐operative hospitalization was independently associated with an increased risk of a post‐operative infection [adjusted odds ratio (aOR): 1.61, 95% confidence interval [CI]: 1.06–2.46] and SSI (aOR: 1.79, 95% CI: 1.07–2.97). Pre‐operative hospitalization was also associated with an increased risk of post‐operative infections resistant to standard pre‐operative antibiotics (OR: 2.64, 95% CI: 1.06–6.59) and an increased risk of resistant SSIs (OR: 3.99, 95% CI: 1.25–12.73). Discussion: Pre‐operative hospitalization is associated with an increased incidence of post‐operative infections, often with organisms that are resistant to surgical chemoprophylaxis. Patients hospitalized up to 1 year before HPB surgery may benefit from extended spectrum chemoprophylaxis.